Introduction to Special Issue: The Future of Revelation and Gender Studies - Fletcher, Michelle (Journal for the study of the New Testament, 2025)
This introduction lays out the premise for this special edition, which arose from a panel session at the 2024 Society of Biblical Literature Annual Meeting which explored ‘The Future of Revelation and Gender Studies’. It explains how those included in the volume build on previous trends in scholarship and offer insights into avenues they would like to see further research on in relation to Revelation and gender take. Taken together, the pieces offer a rich set of diverse perspectives on the book of Revelation and its study in relation to gender.